Insomnia Caused by Serotonin Depletion is Due to Hypothermia - Murray, Nicholas M. (Sleep, 2015)
STUDY OBJECTIVE: Serotonin (5-hydroxytryptamine, 5-HT) neurons are now thought to promote wakefulness. Early experiments using the tryptophan hydroxylase inhibitor para-chlorophenylalanine (PCPA) had led to the opposite conclusion, that 5-HT causes sleep, but those studies were subsequently contradicted by electrophysiological and behavioral data. Here we tested the hypothesis that the difference in conclusions was due to failure of early PCPA experiments to control for the recently recognized role of 5-HT in thermoregulation. DESIGN: Adult male C57BL/6N mice were treated with PCPA (800 mg/kg intraperitoneally for 5 d; n = 15) or saline (n = 15), and housed at 20°C (normal room temperature) or at 33°C (thermoneutral for mice) for 24 h. In a separate set of experiments, mice were exposed to 4°C for 4 h to characterize their ability to thermoregulate. MEASUREMENTS AND RESULTS: PCPA treatment reduced brain 5-HT to less than 12% of that of controls. PCPA-treated mice housed at 20°C spent significantly more time awake than controls. However, core body temperature decreased from 36.5°C to 35.1°C. When housed at 33°C, body temperature remained normal, and total sleep duration, sleep architecture, and time in each vigilance state were the same as controls. When challenged with 4°C, PCPA-treated mice experienced a precipitous drop in body temperature, whereas control mice maintained a normal body temperature. CONCLUSIONS: These results indicate that early experiments using para-chlorophenylalanine that led to the conclusion that 5-hydroxytryptamine (5-HT) causes sleep were likely confounded by hypothermia. Temperature controls should be considered in experiments using 5-HT depletion. CITATION: Murray NM, Buchanan GF, Richerson GB. Insomnia caused by serotonin depletion is due to hypothermia. SLEEP 2015;38(12):1985–1993.